PENERAPAN SISTEM BUDIDAYA HIDROPONIK VERTIKULTUR DAN KONVENSIONAL DI SEKOLAH DASAR NEGERI 3 TANJUNG PURWOKERTO JAWA TENGAH - Hadi, S. N.; Dewi, P. S.; Widiyawati, I. (Buletin Udayana Mengabdi; Vol 21 No 1 (2022): Buletin Udayana Mengabdi, 2022)
The target audience for Community Service (PKM) activities were teachers and students of SDN 3 Tanjung Purwokerto, Central Java. The problems that exist were (1) the school's vacant land has not been optimized, (2). The school has a vision to become a Adiwiyata school, but there are no supporting activities, (3). Knowledge of various cultivation techniques for vegetables and various vegetables that are important for the immune system during the Covid-19 pandemic is still limited, (4). Knowledge of various types of food made from delicious, interesting, and modern vegetables is still limited. The objectives of the activity were (1). Supporting the vision of the school to become a Adiwiyata school by transferring vegetable cultivation technology with hydroponic, verticulture, and conventional techniques, (2). Providing education on a variety of vegetables and their benefits for the immune system, (3). Show off a variety of interesting, tasty, and modern vegetable-based foods. The method used is a participatory approach which includes education, training, mentoring, and demonstration plots. The results showed that all activities can run well with the support of teachers and students. Plants cultivated using hydroponic, verticulture, and conventional techniques can grow well until harvesting. The target audience knows a variety of vegetables that are important for the immune system, especially during the Covid-19 pandemic. The target audience knows that vegetables can be made into a variety of foods such as ice cream, burgers and spaghetti.   Keywords: hidroponic, verticulture, SDN 3 Tanjung, Adiwiyata Schoo